Comparison of the anthropometric and physical characteristics of international and provincial rugby sevens players - Ross, A.; Gill, N. D.; Cronin, J. B. (International Journal of Sports Physiology and Performance, 2015)
Anthropometrical and physical characteristics have been used to distinguish players of different competition levels and position groups; however, there is no literature on rugby sevens. Purpose: To compare the anthropometrical and physical characteristics of international and provincial rugby sevens players and between forwards and backs. Methods: To assess whether differences exist, 65 rugby sevens players including 22 international players and 43 provincial-level players were assessed for height, mass, body composition, speed, repeated-sprint ability, lower-body power, upper-body strength, and maximal aerobic endurance during in-season preparation for tournaments. Results: Clear differences (2.8-32%; small to very large effect sizes) were observed in all anthropometrical and physical measures between international and provincial players, with the largest differences observed in repeated-sprint ability (5.7%; very large effect size), 40-m-sprint time (4.4%; large effect size), 50-kg squat-jump peak power (32%; large effect size), and multistage fitness-test performance (19%; large effect size). Fewer and smaller differences (0.7-14%; trivial to large effect sizes) were found when comparing forwards and backs, with body height being the most discriminant characteristic (3.5%; large effect size). Conclusions: Lower-level rugby sevens players should seek to improve their overall physical profile, particularly their repeated-sprint ability, to reach higher levels in rugby sevens. Furthermore, positional status may have little importance when preparing for rugby sevens.